PENGARUH PROFITABILITAS, SIZE, LEVERAGE DAN CAPITAL INTENSITY RATIO TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015 - 2019 - Sri Mulyani; Milka Susana Theorupun; Yunita Niqrisah Dwi Pratiwi (EKOBIS, 2021)
This study aims to examine the effect of profitability, size, leverage, and capital intensity ratio on tax avoidance. This study focuses on the Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 – 2019 with a population of 77 companies. Determination of the number of samples using purposive sampling method, in order to obtain a sample of 16 companies. Hypothesis testing is done by using multiple analysis techniques. The hypothesis testing method uses a significant level of 5%. This study obtained the first result, the profitability variable has a negative and insignificant effect on tax avoidance. The second result, the variable size has a positive and significant effect on tax avoidance. The third result, the leverage variable has a positive and insignificant effect on tax avoidance. The fourth result, the variable capital intensity ratio has a positive and insignificant effect on tax avoidance. Profitability, size, leverage, and capital intensity simultaneously affect tax avoidance.